2016
DOI: 10.1007/s11104-016-2798-0
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of nitrogen leaching from organic layers in Central European beech forests

Abstract: Background and Aims: The response of forest ecosystems to continuous nitrogen (N) deposition is still uncertain. We investigated imports and exports of dissolved N from mull-type organic layers to identify the controls of N leaching in Central European beech forests under continuous N deposition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 54 publications
(86 reference statements)
1
6
0
Order By: Relevance
“…1), a quantification of the saturation of exchange sites with NH 4 is not possible for NFSI. In the mineral soil, soil solution concentrations of NH 4 are usually very low due to retention in the organic layer and nitrification Schwarz et al 2016). Corre et al (2007) found for German forest sites on a N deposition gradient, that microbial NH 4 retention was more important than abiotic NH 4 retention.…”
Section: Base Saturationmentioning
confidence: 99%
“…1), a quantification of the saturation of exchange sites with NH 4 is not possible for NFSI. In the mineral soil, soil solution concentrations of NH 4 are usually very low due to retention in the organic layer and nitrification Schwarz et al 2016). Corre et al (2007) found for German forest sites on a N deposition gradient, that microbial NH 4 retention was more important than abiotic NH 4 retention.…”
Section: Base Saturationmentioning
confidence: 99%
“…Soil nitrification is likely favored by NH4 + addition as a portion of DN from throughfall. The ratio of NH4 + to NO3is known to decrease from throughfall to soil leachate (Schwarz et al, 2016), suggesting that a fraction of the incoming NH4 + is either immobilized by binding to soil minerals or by uptake into microbial biomass, or is transformed to NO3by nitrification. In addition, fluxes of total nitrogen (TN) showed a strong increase from spring to autumn 2018, indicating that drought also enhanced the export of nitrogen from soil (personal communication)…”
Section: Discussionmentioning
confidence: 99%
“…Soil quality is a key factor for supporting plant growth and ultimately affecting ecosystem services, including soil carbon (C) sequestration, purifying water by nutrient retention, and maintaining structure and stability of landscape patterns (Doran & Zeiss, 2000; Oren et al, 2001). However, in highly managed plantation forests, low ground cover (in terms of areal coverage) and low diversity may alter soil properties (Lange et al, 2015; Schwarz et al, 2016), resulting in decreasing soil function. This problem is even more serious in landscaped forest in scenic areas, which experience intensive human activity.…”
Section: Introductionmentioning
confidence: 99%
“…Urban greening policies have been designed with a goal of improving soil function (Feng et al, 2021; Jones, 2021; Nidzgorski & Hobbie, 2016). While most attention has been focused on overstory trees, the functional diversity of forest understory plants also plays an important role in ecosystem function, including C sequestration and nutrient cycling (Chen, Zhang, et al, 2019; Leppälammi‐Kujansuu et al, 2014; Schulze et al, 2009; Schwarz et al, 2016; Wu et al, 2011). Because urban greening projects often neglect understory plants, research on the influences of different understory vegetation on soil properties is needed in order to provide information for vegetation design and management to improve ecosystem services.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation